Physicochemical and Organoleptic Characteristic of Velva with Variation Sweet Potatoes Types (Ipomea batatas) and Addition of Extract Kecombrang Flower (Etlingera elatior): Karakteristik Fisikokimia dan Organoleptik Velva dengan Variasi Jenis Ubi Jalar (Ipomea batatas) dan Penambahan Ekstrak Bunga Kecombrang (Etlingera elatior) - Siti Rosiyah Mahmuddah; Yannie Asrie Widanti; Merkuria Karyantina (Agrobiotek, 2024)
Velva is frozen food product has low fat and made from crushed fruit or vegetables that has a similar texture like ice cream. Sweet potatoes used as a raw material it is an innovation of food processing to increase economic value. The addition of kecombrang extract creates a new taste and has a lot of nutritional content such us high antioxidant. The research of objective is to determine the characteristic of velva varietas of sweet potatoes and addition of kecombrang flower extract based on longest melting power and highest total dissolved solids. The research using completely randomized with 2 factorial. First factor is type of sweet potatoes ( white, orange, purple) and second factor is addition of kecombrang flower extract (5%, 10% and 15%). The results of chemical (moisture content, antioxidant activity) and physical parameters (overrun, melting time and total dissolved solids) based on longest melting power and highest total dissolved solids formulation is purple sweet potatoes and 15% kecombrang extract is water content 67,37%, antioxidant 74,24%, overrun 22,18%, melting time 18,54 minutes, total dissolved solids 25,7oBrix. Based on the most preferred organoleptic paramaters is purple sweet potatoes and 5% kecombrang extract is water content 69,09%, antioxidant 66,41%, overrun 23,79%, melting time 17,28 minutes, total dissolved solids 23,6oBrix